Hubungan Kemampuan Interaksi Sosial Dengan Perilaku Bullying Pada Siswa SMP N 40 Kota Batam - Anisa Syafitri Ramadhani; Rachmawaty M Noer; Mira Agusthia (STIKes Ibnu Sina Ajibarang, 2023)
Social interaction skills are very necessary in the surrounding environment because social interaction influences many things, one of which is individual behavior. If the individual has good social interaction skills then adaptation to the environment and behavior will be good. The phenomenon that occurs in many schools is that students with poor social interaction skills influence their behavior, where bullying behavior occurs. This research aims to determine the relationship between social interaction skills and bullying behavior of students at SMP N 40 Batam City. This research method is correlational with a sample size of 201 respondents. The research results showed that the average of students who experienced social interaction skills was in the good range, namely 101 respondents (50.2%) and bullying behavior was also found in the high category, namely 104 respondents (51.7%). The results of this research using chi square test analysis showed that there was a relationship between students' social interaction abilities and bullying behavior in students at SMP N 40 Batam City. The conclusion is that there is a relationship between social interaction skills and bullying behavior in students at SMP N 40 Batam City in 2023. Suggestions for students to further improve their social interaction skills, especially in the environment to avoid bullying behavior because if bullying behavior occurs, students will experience difficulties in interacting with each other. each other.